2006
DOI: 10.1063/1.2369636
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmotic flow and mixing in microchannels with the lattice Boltzmann method

Abstract: Understanding the electroosmotic flow in microchannels is of both fundamental and practical significance for the design and optimization of various microfluidic devices to control fluid motion. In this paper, a lattice Boltzmann equation, which recovers the nonlinear Poisson-Boltzmann equation, is used to solve the electric potential distribution in the electrolytes, and another lattice Boltzmann equation, which recovers the Navier-Stokes equation including the external force term, is used to solve the velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…This flow phenomenon was observed experimentally by Stroock et al (2000). In later studies, these induced localized circulations in the steady flow field were successfully employed to improve species mixing in a microchannel (Erickson and Li 2002;Chang and Yang 2004;Fushinobu and Nakata 2005;Wang et al 2005a;Tang et al 2006) or a curved microchannel (Lin et al 2006). However, chaotic mixing was absent in the proposed mixers since the zeta potential was time-independent and hence the induced circulations were closed and steady in two-dimensional flow systems.…”
Section: Heterogeneous Surface Charge Patterning Enhanced Electroosmomentioning
confidence: 92%
See 1 more Smart Citation
“…This flow phenomenon was observed experimentally by Stroock et al (2000). In later studies, these induced localized circulations in the steady flow field were successfully employed to improve species mixing in a microchannel (Erickson and Li 2002;Chang and Yang 2004;Fushinobu and Nakata 2005;Wang et al 2005a;Tang et al 2006) or a curved microchannel (Lin et al 2006). However, chaotic mixing was absent in the proposed mixers since the zeta potential was time-independent and hence the induced circulations were closed and steady in two-dimensional flow systems.…”
Section: Heterogeneous Surface Charge Patterning Enhanced Electroosmomentioning
confidence: 92%
“…Recently, the lattice Boltzmann (LB) equation has been proven useful for the description of mesosystems with complicated geometry and composition (Succi 2001). Hence, it also has been widely used over the past years to describe the electrokinetic flow field and mixing (Tian et al 2005;Wang et al 2005aWang et al , 2006aTang et al 2006), which is solved through the so-called lattice Boltzmann method (LBM).…”
Section: Basic Methodologymentioning
confidence: 99%
“…For example, numerical simulations by Tang et al (2006) indicate that a proper combination of electroosmotic flow and pulsatile flow can achieve complete mixing of two microchannel flows. Stroock et al (2002) and Glasgow and Aubry (2003) observed that inertial effects become important for microfluidic mixing for Re ) 1, which is the case studied here.…”
Section: Introductionmentioning
confidence: 98%
“…However, for the pressure-driven flow, the entire cross section of the channel experiences the pressure-driven force. As noted in our previous work [24], the velocity profile for Newtonian flow behaves plug-like when the ratio of the channel height to the Debye length is larger than about 10. It can also be observed from Fig.…”
Section: Electroosmotic Channel Flowmentioning
confidence: 77%
“…The following discrete lattice Boltzmann evolution equation for the electric potential has been derived by [9,24] g i (r + c i ı t , t + ı t )…”
Section: The Lattice Boltzmann Equation For Electric Potentialmentioning
confidence: 99%